Prevalência de má oclusão, cárie e padrão facial em escolares de cinco e doze anos de João Pessoa-Paraíba - Pereira, Tiago Batista (2014)
The aim of this study was to determine the prevalence of malocclusion , tooth decay and facial pattern in children 05 to 12 years and to investigate a possible association between these variables. This cross-sectional study in a sample of 71 students aged 05 years and 240 students of 12 years and enrolled in municipal schools in João Pessoa, Paraíba. The sample selection was by geographic population clusters randomly to schools, individuals and systematic. Examinations for dental caries , overbite , overjet , non-nutritive sucking habits, insertion of labial frenulum , key canines , crossbite , molar terminal plane , facial pattern ( PF ) and the Dental Aesthetic Index ( DAI ) were performed according to age indicated . All examinations were performed by a single calibrated examiner ( kappa> 0.74 for all variables ). Bivariate analyzes (chi- square and Fisher's exact test) and multivariate (p < 0.05 ) were performed. There were 36.6 % of students with at least five years a caries lesion. The mean (SD) dmft was 2.63 (3.9). The canine relationship class I (67.9 %) was the most frequent. The malocclusion was represented by the overbite (55.2 %), overjet ( 43.14 ) % and posterior crossbite (17.31%). Predominant facial pattern (PF) II (68.3%). Gender was significantly associated to the variables (key canines, overjet and molar terminal plane) (p < 0.05 ). In school 12 years was 35 % in at least one carious lesion. The mean (SD) DMFT was 1.74 (2.40 ) , with the most significant decay component (63.5 %). Malocclusion affects 32% of the sample. Pattern II facial predominated (57 %). Gender was not significantly associated with the study variables (p> 0.05). although the female has made 65.9% of poor / very severe severe occlusions . In the regression model it was observed that poor very severe occlusion, proximal caries , lack of lip seal at rest , nonnutritive sucking , overjet and mandibular jaw misalignment, crowding may influence the PF (p<0.05). Within the limitations of this study, it was concluded that the study population has a prevalence of dental caries considered a moderate to low prevalence of malocclusion, and predominance of facial pattern II. The age group of 05 years has been more prevalent as PF II and the 12-year prevalence of PF I and II. The observed data are indicative of the higher caries experience may be related to the facial pattern I becoming a variable potentially interfere with the reduction of malocclusion and change the pattern of facial growth . It was also observed that non-nutritive sucking , active labial frenulum , greater crowding , dmft and proximal caries , may influence the establishment of the facial pattern of individuals 5 years.